Bloodsucking Insects - P.G. Koehler; J.L. Castner (EDIS)
This document provides an overview of bloodsucking insects in Florida, detailing their physical characteristics, behaviors, and habitats. It covers mosquitoes, flies, lice, and true bugs, highlighting species such as the Asian tiger mosquito, stable fly, horse fly, deer fly, sand fly, head louse, pubic louse, bed bug, and bloodsucking conenose. Each section emphasizes unique features, such as the Asian tiger mosquito’s daytime biting habits and the stable fly’s bayonet-like proboscis. The document aims to educate readers on identifying and understanding these parasitic insects. Date first printed: November 1992.